2013
DOI: 10.1038/cddis.2013.352
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reuptake of granzyme B leads to emperitosis: an apoptotic cell-in-cell death of immune killer cells inside tumor cells

Abstract: A cell-in-cell process refers to the invasion of one living cell into another homotypic or heterotypic cell. Different from non-apoptotic death processes of internalized cells termed entosis or cannibalism, we previously reported an apoptotic cell-in-cell death occurring during heterotypic cell-in-cell formation. In this study, we further demonstrated that the apoptotic cell-in-cell death occurred only in internalized immune killer cells expressing granzyme B (GzmB). Vacuole wrapping around the internalized ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 33 publications
2
78
0
1
Order By: Relevance
“…As mentioned above, entosis is described a nonapoptotic cell death program in matrix-detached cells initiated by the invasion of one living cell into another [5]. Wang et al report “emperitosis”, an apoptotic cell-in-cell death process that occurs in heterotypic immune killer cells expressing granzyme B inside tumor cells which may serve as an in-cell danger sensation model to prevent the killing of target cells from inside, implying a unique mechanism for tumor cells to escape from immune surveillance [13]. …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, entosis is described a nonapoptotic cell death program in matrix-detached cells initiated by the invasion of one living cell into another [5]. Wang et al report “emperitosis”, an apoptotic cell-in-cell death process that occurs in heterotypic immune killer cells expressing granzyme B inside tumor cells which may serve as an in-cell danger sensation model to prevent the killing of target cells from inside, implying a unique mechanism for tumor cells to escape from immune surveillance [13]. …”
Section: Discussionmentioning
confidence: 99%
“…B cell ingestion in this context resembles "entosis", a mechanism previously found to mediate cell-in-cell structure formation in epithelial cultures and human tumors [7]. Entosis also promotes the uptake of hematopoietic cells into epithelial cells or cancer cells of various types [8,9]. Incredibly, the authors find that entosis-like internalization of latent EBV-infected B cells (Akata) into cultured nasopharyngeal carcinoma cells (CNE-2) leads to the activation of EBV and the transfer of virus to host (CNE-2) cells.…”
mentioning
confidence: 71%
“…The pathway of the first two cell-in-cell deaths is lysosome-dependent cell death [6, 7], and the third one, which is elucidated and termed by us, is a typical caspase-dependent cell death [1, 8, 13]. Interestingly, we found that different immune cells may choose their ways to die inside tumor cells.…”
Section: Cell-in-cell Phenomenon Is Diverse and Evolutionarily Conservedmentioning
confidence: 84%